Exploring F/CF3 substituted oxocarbenium ions for the diastereoselective assembly of highly substituted tetrahydrofurans. Issue 27 (20th March 2023) - Fernandes, Anthony J.; Michelet, Bastien; Panossian, Armen; Martin-Mingot, Agnès; Leroux, Frédéric R.; Thibaudeau, Sébastien
Abstract : We report on the dramatic effect of a local partial charge inversion by replacing a CHCH3 group by a CFCF3 . This strategy allows the diastereoselective reduction of 5-membered ring oxocarbenium ions to access highly substituted tetrahydrofurans. Abstract : Understanding the influence of emerging fluorinated motifs is of a crucial importance in the context of the exponentially growing exploitation of fluorine in many fields. Herein, we report on the dramatic effect of a local partial charge inversion by replacing a CHCH3 group by a CFCF3 . This strategy allows the diastereoselective reduction of 5-membered ring oxocarbenium ions to access highly substituted tetrahydrofurans.